TWIK-Related Acid-Sensitive Potassium Channels (TASK-1) Emerge as Contributors to Tone Regulation in Renal Arteries at Alkaline pH - Shvetsova, Anastasia A.; Lazarenko, Varvara S.; Gaynullina, Dina K.; Tarasova, Olga S.; Schubert, Rudolf (Frontiers in Physiology, 2022)
Aim: TASK‐1 channels are established regulators of pulmonary artery tone but their contribution to the regulation of vascular tone in systemic arteries is poorly understood. We tested the hypothesis that TASK-1 channel functional impact differs among systemic vascular beds, that this is associated with differences in their expression and may increase with alkalization of the extracellular environment. Therefore, we evaluated the expression level of TASK-1 channels and their vasomotor role in mesenteric and renal arteries. Methods: Pulmonary, mesenteric and renal arteries from male Wistar rats were used for TASK-1 channel mRNA (qPCR) and protein content (Western blotting) measurements. The functional role of TASK-1 channels was studied by wire myography using the TASK-1 channel blocker AVE1231. In some experiments, the endothelium was removed with a rat whisker. Results: Expression levels of both mRNA and protein of the TASK-1 channel pore-forming subunit were highest in pulmonary arteries, lowest in mesenteric arteries and had an intermediate value in renal arteries. Blockade of TASK-1 channels by 1 µM AVE1231 increased U46619-induced contractile responses of pulmonary arteries but did not affect basal tone and contractile responses to methoxamine of mesenteric and renal arteries at physiological extracellular pH (pHo = 7.41). At alkaline extracellular pH=7.75 (increase of NaHCO3 to 52 mM) AVE1231 evoked the development of basal tone and increased contractile responses to low concentrations of methoxamine in renal but not mesenteric arteries. This effect was independent of the endothelium. Conclusion: In the rat systemic circulation, TASK-1 channels are abundant in renal arteries and have an anticontractile function under conditions of extracellular alkalosis.